IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SDN 2 KALIWENANG KABUPATEN GROBOGAN - Ardhan Helfrid Tontowi; Mei Fita Asri Untari; Kiswoyo Kiswoyo (Wawasan Pendidikan, 2022)
This research is motivated by the diverse needs of students in learning, the needs of teachers in carrying out learning activities, and other staff in their professional development. The purpose of this research is to know the process of implementing School-Based Management at SDN 2 Kaliwenang and to find out the supporting and inhibiting factors in the implementation of School-Based Management at SDN 2 Kaliwenang. This research method is descriptive qualitative, researchers carry out activities by describing data and facts by finding existing realities and carried out continuously from the beginning to the end of the study. The results of this study showed that the implementation process of School-Based Management at SDN 2 Kaliwenang includes the effectiveness of the learning process, strong school leadership, effective management of personnel, the school has independence, participation of school and community members and school transparency. Supporting factors in the implementation of School-Based Management at SDN 2 Kaliwenang include financial, human resources and their thoughts as well as facilities and infrastructure. Meanwhile, the obstacles in implementing School-Based Management at SDN 2 Kaliwenang include school management, community participation and teaching and learning activities.